Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/htj.21227
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Impact of DBD Plasma Actuators on Temperature Enhancement in the Channel Flow

Abstract: The present study indicates the impact of different arrangements of dielectric barrier discharge (DBD) plasma actuators on temperature field in a channel flow. The modified lumped circuit element electro-static model was used to calculate induced Lorentz body force and plasma dissipation of the actuators. Different distributions of temperature in the modeled channel flow for each arrangement of actuators (one, two, and three attached actuators) are discussed. According to the numerical simulation, DBD plasma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Most studies dealing with the thermal effects of dielectric barrier discharge have been performed experimentally, but some numerical studies can also be found in the literature. Aberoumand et al [170] numerically investigated the effects of various DBD plasma actuator arrangements on the temperature field in a channel flow, and Benmoussa et al [171] numerically investigated the phenomenon of gas heating in dielectric barrier discharges due to the Joule heat effect for Ne-Xe gas mixtures. Recently, Zhang et al [172] conducted a detailed review of recent developments in the thermal properties of dielectric barrier discharge surface plasmas and demonstrated the potential of these devices to produce significant thermal effects that can be used for deicing and ice prevention applications.…”
Section: Dbd Plasma Actuators' Applicationsmentioning
confidence: 99%
“…Most studies dealing with the thermal effects of dielectric barrier discharge have been performed experimentally, but some numerical studies can also be found in the literature. Aberoumand et al [170] numerically investigated the effects of various DBD plasma actuator arrangements on the temperature field in a channel flow, and Benmoussa et al [171] numerically investigated the phenomenon of gas heating in dielectric barrier discharges due to the Joule heat effect for Ne-Xe gas mixtures. Recently, Zhang et al [172] conducted a detailed review of recent developments in the thermal properties of dielectric barrier discharge surface plasmas and demonstrated the potential of these devices to produce significant thermal effects that can be used for deicing and ice prevention applications.…”
Section: Dbd Plasma Actuators' Applicationsmentioning
confidence: 99%
“…They studied the temperature distribution and proposed an hypothesis on the mechanism of dielectric heating and a relationship between dielectric surface temperature and gas temperature. Aberoumand et al [39] numerically studied the impact of different arrangements of dielectric barrier discharge plasma actuators on temperature field in a channel flow. The actuators were tested under an incompressible flow regime with a constant entrance Reynolds number.…”
Section: Introductionmentioning
confidence: 99%